A qualitative study assessing acceptability and appropriateness of a technology-assisted mental health intervention by community frontline workers: mPareshan implementation research in rural Pakistan - Samina Akhtar; Fauziah Rabbani; Javeria Nafis; Amna Siddiqui; Zul Merali (BMC Psychiatry)
Abstract Background With a shortage of mental health specialists and a significant rural population in Pakistan, leveraging community-based healthcare workers becomes crucial to address mental health needs. Equipping the healthcare workers with digital tools such as mobile applications have the potential to increase access to mental health support in low-resource areas. This study examines the acceptability, appropriateness, barriers, and facilitators to implementing a technology-assisted mental health intervention (mPareshan) delivered by Lady Health Workers (LHWs) in rural Pakistan. Methods This is a qualitative study embedded within a larger implementation research trial assessing the feasibility of an mHealth intervention aimed at improving anxiety and depression. 8 focus group discussions and 18 in-depth interviews were conducted. Perceptions were sought before and after intervention from stakeholders comprising of policymakers, LHWs, Lady Health Supervisors (LHSs), and community participants. Data underwent thematic analysis using the RE-AIM framework. Results Six main themes emerged from the data. All participants had realization of rising burden of mental illnesses and identified key determinants for mental ill-health. Delivery of mental health counselling by LHWs through a technology-assisted intervention was deemed acceptable and appropriate. LHWs were considered capable and trustworthy by the community to deliver a home-based mHealth intervention, given their easy accessibility as residents of the same community. The technology demonstrated potential for easy adoption as these frontline health workers were already familiar with smartphone technology. Some barriers identified during implementation roll-out included heavy workload of LHWs and difficulty in internet connectivity. Use of videos for counselling, and supportive supervision by LHSs emerged as key facilitators for implementation. Conclusion This study highlights that a technology-focused mental health intervention is feasible, acceptable, and appropriate to be implemented by community frontline workers in resource-constrained rural Pakistani settings. The mPareshan intervention can be easily adopted within the LHW-P. Further research should investigate how implementation barriers can be addressed for successful delivery.